2003
DOI: 10.1074/jbc.m308857200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Novel Human β1,4-N-Acetylgalactosaminyltransferase, β4GalNAc-T3, Responsible for the Synthesis of N,N′-Diacetyllactosediamine, GalNAcβ1–4GlcNAc

Abstract: We found a novel human glycosyltransferase gene carrying a hypothetical ␤1,4-glycosyltransferase motif during a BLAST search, and we cloned its full-length open reading frame by using the 5 -rapid amplification of cDNA ends method. It encodes a type II transmembrane protein of 999 amino acids with homology to chondroitin sulfate synthase in its C-terminal region (GenBank TM accession number AB089940). Its putative orthologous gene was also found in mouse (accession number AB114826). The truncated form of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 51 publications
(46 reference statements)
4
78
0
Order By: Relevance
“…B4GALNT3 modifies N-and O-glycans decorated with GlcNAc in vitro. 7 In the present study, we found that B4GALNT3 adds LacdiNAc to ␤ 1 integrin and, thereby, suppresses its downstream signaling. Glycolipids on the cell surface may interact with functional membrane proteins, such as integrins, growth factor receptors, and Src family kinases to form glycosynaptic microdomains that control cell adhesion, growth, and motility.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…B4GALNT3 modifies N-and O-glycans decorated with GlcNAc in vitro. 7 In the present study, we found that B4GALNT3 adds LacdiNAc to ␤ 1 integrin and, thereby, suppresses its downstream signaling. Glycolipids on the cell surface may interact with functional membrane proteins, such as integrins, growth factor receptors, and Src family kinases to form glycosynaptic microdomains that control cell adhesion, growth, and motility.…”
Section: Discussionsupporting
confidence: 55%
“…7 This enzyme can transfer GalNAc to any nonreducing terminal GlcNAc-␤ in vitro, resulting in synthesis of GalNAc␤1, 4GlcNAc (LacdiNAc or LDN). The terminal ␤1,4 -linked GalNAc of LDN can be recognized by a lectin, Wisteria floribunda agglutinin (WFA).…”
Section: ␤14-n-acetylgalactosaminyltransferase III (B4galnt3)mentioning
confidence: 99%
“…By evaluating alkaline phosphatase activity in glycan-related gene knockdown mESCs, LacdiNAc, which is synthesized by b4GalNAc-T3 [35], was identified as a candidate cell surface glycan required for self-renewal of mESCs. We designed two constructs that expressed different shRNAs targeting b4GalNAc-T3 (b4GalNAc-T3-1 and b4GalNAc-T3-2), as described previously [40], and additionally constructs that expressed shRNAs targeting EGFP as negative controls.…”
Section: Lacdinac Contributes To Self-renewal Of Mescsmentioning
confidence: 99%
“…By evaluation of alkaline phosphatase activity in RNAi-mediated knockdown mESCs, we identified glycans essential for selfrenewal. One of the glycan sequences of interest is the LacdiNAc (GalNAcb1-4GlcNAc) motif, which is synthesized by b4GalNAc-T3 [35]. LacdiNAc is frequently present on glycoproteins and glycolipids in invertebrates but is only present on a limited number of glycoproteins and glycolipids, such as glycoprotein hormones, in vertebrates [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…b4GalNAc-T3 has been shown to be significantly expressed in the gastrointestinal tract (14). In addition, the recombinant enzyme can transfer GalNAc to GlcNAc and form N,N ¶-diacetyllactosediamine (GalNAch1,4GlcNAc) in both N-and O-glycans by an in vitro enzyme activity assay.…”
Section: Introductionmentioning
confidence: 99%